Ketorolac vs. tramadol for pain management after abdominal surgery in children - Iman Hendarman; Silvia Triratna; Muhammad Kamaludin; Theodorus Theodorus (Paediatrica Indonesiana, 2014)
Background Tramadol is a pure analgesic widely used forpostoperative treatment and well tolerated by children. Howevet;it has only a 50% efficacy. Ketorolac, a nonô€™steroid anriô€™inflammation drug (NSAID), is widely used in adults and has upto 85% clinical efficacy. Data supporting the use of ketorolac inchildren has been limited.Objective To compare the clinical efficacies of intravenousketorolac and tramadol for moderateô€™toô€™severe pain managementafter abdominal surgery in children.Methods A doubleô€™blind controlled trial was conducted in Moh.Hoesin Hospital, Palembang, from January to June 2012. Subjectswere postoperative children aged 1 ô€™ 7 years who met the inclusioncriteria. T hey were randomized into two groups who receivedeither intravenous ketorolac or tramadol. Subjects assessedtheir pain level using the Face, Legs, Anns, Cry and Consolability(FLACC) pain scale. T he FLACC scores ::::;3 were considered toindicate clinical success of the intervention. Data were analyzedby Tô€™test, Chiô€™square test, and Fischer's exact test.Results Of the 60 subjects who underwent abdominal surgery withgeneral anesthesia, 31 (52%) were boys and 29 (48%) were girls.Subjects' mean age and body weight were 3.7 (SD 1.82) years and12.6 (SD 2.85) kg, respectively. Mean duration of surgery was 71.7(SD 21.11) minutes and mean postô€™operative FLACC score was6.6 (SD 0.5). Eight subjects dropped out of the study. Efficacies ofketorolac and tramadol were not significantly different at 21/26 and17/26, respectively (P=OJ5). In addition, there was no significantdifference in the number of patients experiencing a >3 FLACCscore decline between ketorolac and tramadol groups (P=0.61).Conclusion T here is no significant difference in the efficaciesof intravenous ketorolac and tramadol for moderateô€™toô€™severepain management after abdominal surgery in children. [PaediatrIndones.2014;54:118.21.].